2020
DOI: 10.1108/intr-03-2019-0112
|View full text |Cite
|
Sign up to set email alerts
|

Is boredom proneness related to social media overload and fatigue? A stress–strain–outcome approach

Abstract: PurposeSocial media overload and fatigue have become common phenomena that are negatively affecting people's well-being and productivity. It is, therefore, important to understand the causes of social media overload and fatigue. One of the reasons why many people engage with social media is to avoid boredom. Thus, the purpose of this paper is to investigate how boredom proneness relates to social media overload and fatigue.Design/methodology/approachBuilding on the stress–strain–outcome framework, this paper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 88 publications
5
77
0
2
Order By: Relevance
“…Prior literature has found that communication overload can have negative consequences such as decreased work productivity (Mcfarlane & Latorella 2002) as well as increased fatigue (Klapp 1986). In the social media use context, several prior studies reported communication overload as a major source of social media fatigue (see Lee et al, 2016;Whelan et al, 2020a). Consequently, we hypothesize the following.…”
Section: H3 Information Overload Will Have a Positive Influence On Smentioning
confidence: 85%
“…Prior literature has found that communication overload can have negative consequences such as decreased work productivity (Mcfarlane & Latorella 2002) as well as increased fatigue (Klapp 1986). In the social media use context, several prior studies reported communication overload as a major source of social media fatigue (see Lee et al, 2016;Whelan et al, 2020a). Consequently, we hypothesize the following.…”
Section: H3 Information Overload Will Have a Positive Influence On Smentioning
confidence: 85%
“…Once humans are fatigued, it reduces their ability to make sense of the situation they are in, and hinders their judgement and decision making, for example, with regards to what news is backed up by journalistic rigour and what is not. Applying such scenarios to the COVID-19 pandemic suggests when humans are overloaded with information, they are less likely to go through the extra trouble of verifying information sources (Whelan et al, 2020b). Thus, we hypothesise the following.…”
Section: Effects Of Online Informationmentioning
confidence: 95%
“…As an example, there is evidence that information-seeking during pandemics is more common in those experiencing worry or fear (Lin et al, 2014). Similarly, previous research suggests that when in a state of fear or distress, peoples' usage patterns and perceptions of social media alters significantly to the extent they can become overloaded and fatigued (Maier et al, 2014;Whelan et al, 2020b). Building on this existing work, we investigate the drivers of COVID-19 specific misinformation and cyberchondria.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Employee interactions with enterprise social media collaboration endpoints such as Yammer, Slack and Google docs have also been cited as antecedents to communication overload [see Whelan et al, 2017]. The ubiquitous nature of these services makes them ripe for overuse given that they can be accessed via mobile devices.…”
Section: The Modalitymentioning
confidence: 99%